Decision-making about participation in colorectal cancer screening in Sweden: Autonomous, value-dependent but uninformed?. Issue 4 (April 2021) - Wangmar, Johanna; Wengström, Yvonne; Jervaeus, Anna; Hultcrantz, Rolf; Fritzell, Kaisa
Highlights: CRC screening decisions in Sweden appear to be largely uninformed. Values and preferences seem to play an important role in decision-making. Most Swedes decide about screening participation without involving others. Abstract: Objective: To investigate knowledge, values and preferences, and involvement among screening participants and non-participants in relation to colorectal cancer (CRC) and screening decision. Methods: Individuals (N = 2748) from the Screening of Swedish Colons trial were invited to respond to the SCREESCO questionnaire, assessing information/knowledge, values/preferences, and involvement. Results: Respondents' (screening participants, n = 1320; non-participants, n = 161) knowledge varied across items; 90 % recognised faecal blood as a CRC symptom, but less than half cited overweight, smoking, alcohol, and physical inactivity as risk factors. Incidence and case fatality were often over- and underestimated, respectively (>45 and 40 %). Non-participants were more uncertain about their CRC risk (p = 0.015) and less convinced that screening reduces the risk of dying from CRC (p < 0.001). In decision-making, screening participants took most into consideration the importance of early detection and CRC worry, and non-participants the risk of discomfort and complications due to the screening examination (p < 0.001). Most individuals made the decision without involving others. Conclusion: For informed and shared decisions, efforts need to be made to increase public knowledge about CRC and to develop interventions to support individuals in decision-making. Practice implications: These results can inform and guide future initiatives to facilitate high quality decisions and CRC screening uptake in Sweden.